2021
DOI: 10.1007/s13410-021-00997-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of bacteria from diabetic foot ulcer: amputation, antibiotic resistance and mortality rate

Abstract: Background Diabetic foot ulcer (DFU) is one of the most serious complications of diabetes mellitus with devastating outcomes. Poorly treated DFU leads to osteomyelitis, gangrene and limb amputation. There is an increased risk of mortality for the amputees and increased number of bacterial resistance in survived patients. Struggle on choice of the best antibiotic(s) for DFU is escalating. Objectives To determine risk factors associated with mortality in patients with DFU. To investigate bacterial drug resistanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…The latter probably because gram-negative bacteria are always interpreted as pathogenic bacteria and treated accordingly. The association we found, is in line with the retrospective studies of Lipsky et al and Shaheen et al [ 34 , 35 ]. It is unclear whether gram-negative bacteria increase the risk of mortality directly or indirectly.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The latter probably because gram-negative bacteria are always interpreted as pathogenic bacteria and treated accordingly. The association we found, is in line with the retrospective studies of Lipsky et al and Shaheen et al [ 34 , 35 ]. It is unclear whether gram-negative bacteria increase the risk of mortality directly or indirectly.…”
Section: Discussionsupporting
confidence: 93%
“…Our study confirmed these results, as profile 1 (consisting of Staphylococcus aureus and Streptococcus) and 3 (gram-negative bacteria), were most frequently cultured. In accordance with other studies we found that Streptococcus and Staphylococcus aureus (profile 1) do not increase amputation or mortality risk [ 7 , 8 , 34 , 35 ]. Possible explanations are: the type of infection these bacteria cause, usually acute and mild, as a result of which infection will be recognised in an early stage and treatment starts promptly.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are also consistent with those of similar studies conducted in Kuwait and Lebanon, which found that gramnegative bacteria are more commonly isolated from DFIs, with Escherichia coli being the most common [21,22]. In contrast, Al Ayed et al conducted a study in 2018 on 126 patients aged 40-70 years at the Prince Sultan Military Medical City in Riyadh, Saudi Arabia, using a swab culture method for microbiological testing and reported that Staphylococcus aureus was the most commonly isolated organism, followed by Pseudomonas aeruginosa [23]. The high incidence of gram-negative DFI in our region can be explained by multiple theories.…”
Section: Discussionmentioning
confidence: 99%
“…The decomposition products of diabetic ulcer skin tissue and the persistent high-glucose environment provide an excellent culture medium for the growth and reproduction of bacteria. A large number of bacteria enter the human body through the wound and go deep into the tissue, leading to sepsis and even death ( Shaheen et al, 2021 ; Xie et al, 2022 ). Early, active and effective control can prevent chronic infection and accelerate wound healing ( Han and Kang, 2013 ).…”
Section: Application Of a Nanocomposite Hydrogel Delivery System To D...mentioning
confidence: 99%